2019
DOI: 10.1016/bs.irn.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol drinking exacerbates neural and behavioral pathology in the 3xTg-AD mouse model of Alzheimer's disease

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that represents the most common cause of dementia in the United States. Although the link between alcohol use and AD has been studied, preclinical research has potential to elucidate neurobiological mechanisms that underlie this interaction. This study was designed to test the hypothesis that nondependent alcohol drinking exacerbates the onset and magnitude of AD-like neural and behavioral pathology. We first evaluated the impact of voluntary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 187 publications
(255 reference statements)
4
51
0
2
Order By: Relevance
“…Laboratory findings revealed an increase in Aβ 42/40 ratio in lateral entorhinal and prefrontal cortex, total Tau expression in medial prefrontal cortex, lateral entorhinal cortex, amygdala, and phosphorylated tau expression (Ser 199/Ser 202) in hippocampus. The ADlike pathologies also associated with reduced phosphorylation of phosphoproteins associated with Akt/mTOR signaling pathway in a brain region-specific manner (Hoffman et al, 2019). In agreement with these findings, the Akt/mTOR pathway was reported to respond selectively in a brain region-specific manner in a binge-intake alcohol dependent AUD model (Laguesse et al, 2017).…”
Section: Dementia or Alzheimer's Like Phenotypesmentioning
confidence: 59%
“…Laboratory findings revealed an increase in Aβ 42/40 ratio in lateral entorhinal and prefrontal cortex, total Tau expression in medial prefrontal cortex, lateral entorhinal cortex, amygdala, and phosphorylated tau expression (Ser 199/Ser 202) in hippocampus. The ADlike pathologies also associated with reduced phosphorylation of phosphoproteins associated with Akt/mTOR signaling pathway in a brain region-specific manner (Hoffman et al, 2019). In agreement with these findings, the Akt/mTOR pathway was reported to respond selectively in a brain region-specific manner in a binge-intake alcohol dependent AUD model (Laguesse et al, 2017).…”
Section: Dementia or Alzheimer's Like Phenotypesmentioning
confidence: 59%
“…GSK3β phosphorylation is increased after acute and chronic alcohol exposure. One recent study showed hyperphosphorylation at the GSK3 site on Tau protein in the hippocampus (CA1) subregion of a 3xTg-AD mouse brain 1 month post alcohol drinking, suggesting that chronic alcohol drinking has detrimental effects in AD [35].…”
Section: Studies In Animal and Cell Culture Modelsmentioning
confidence: 99%
“…Higher concentrations of ethanol contribute to increased accumulation/production of Aβ and the precursor protein [34]. One recent study showed that alcohol drinking in the tripletransgenic model of AD (3xTg-AD) mice induced deficits in cognitive and emotional functions compared to wild-type controls, and induced pathological changes such as the hyperphosphorylation of Tau-Ser199/202 in neuronal cell bodies and the dorsal hippocampus (CA1) in 3xTg-AD mice 1 month post alcohol drinking [35]. Alcohol has been suggested to be either protective of, or not associated with PD [36].…”
Section: Introduction and Alcohol Use: Dual Effects And Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations